Optimal High-Order Methods for Solving Nonlinear Equations - S. Artidiello; A. Cordero; Juan R. Torregrosa; M. P. Vassileva (Journal of Applied Mathematics)
A class of optimal iterative methods for solving nonlinear equations is extended up to sixteenth-order of convergence. We design them by using the weight function technique, with functions of three variables. Some numerical tests are made in order to confirm the theoretical results and to compare the new methods with other known ones.